‘Saving Dionysius’: Aquinas’ Exemplary Reception of the Dionysian corpus -a Metacritique. - Darley, Alan Philip (2022)
The enigmatic collection of texts known as the corpus Dionysiacum is well known for sourcing a particular sensibility in theology known as apophatic theology or via negativa which seeks to give due weight to the transcendence of God in relation to the contingencies of human language. This approach has found a new hearing within the contemporary world, especially amongst postmodern and pluralist thinkers, such as Jaques Derrida, Jean-Luc Marion, Catherine Keller, William Franke or John Hick. This thesis explores how Thomas Aquinas’ reception of the Pseudo-Dionysius (who is Thomas’ third most cited authority) might offer a fruitful dialogue or critique of these other receptions. Aquinas is particularly valuable for this role because he is recognised as a foremost Doctor of the Church and a ‘classic’ intellectual defender of orthodoxy. Aquinas notices that the ‘Blessed Dionysius’ writes in an ‘obscure’ fashion and this fact is what permits the divergent receptions to arise. I have schematised these receptions broadly into two streams: one radically agnostic and monistic and the other broadly orthodox. The radically agnostic stream traceable to Plotinus runs through John Scotus Eriugena, Meister Eckhart and Nicholas de Cusa through to Hegel and his followers, whilst the orthodox stream flows through Augustinians like Hugh of St Victor, Denys the Carthusian, Robert Grosseteste and Aquinas. The Eastern orthodox reception also falls within the orthodox stream, except that this also retains some of Dionysius’ own ambiguity in its essence/energies distinction which (as far as the truth of things themselves is concerned), Aquinas helps clarify. This study structures Thomas’ reception around four systematic themes which illustrate the superiority of Thomas’ reading over ‘Plotinian’ receptions old and new, especially allegedly ‘anti-metaphysical’ ones. These themes are Scripture, Language, Knowledge and Hierarchy. Saving Scripture (Chapter 1) is important for illuminating Dionysius’ metaphysics and qualifying the nature of his apophasis against postmodern or pluralist readings of people like Hick or Keller who insist God can be named by any name of which none offers any knowledge claims. For Dionysius, by contrast the ‘names’ of God come from revelation and that revelation is rooted in holy Scripture. I show how Aquinas preserves and clarifies Dionysius’ reverence for Scripture and its metacritical authority over other authorities. Chapter 1 underscores the best paradigm for understanding the historical Dionysius as in some sense an ‘Origenian’ Christian. This is not original as it has been defended in various forms by Perczel, Meyendorff, Kharlamov, Arthur, Ramelli and Golitzin. But the neglect of Origen’s influence on the CD in other works has resulted in an impoverished understanding of its author, his metaphysics and Aquinas’ contribution. Aquinas shares more in common with Dionysius in regard to the Divine inspiration, authority and canon of scripture than do his postmodern readers. He also shares the participatory metaphysics behind Dionysius’ Origenian hermeneutics which saves it from postmodern distortion. But if Dionysius is essentially Origenian; Aquinas is Augustinian which is a kind of reformed Origenianism, hence Augustine frequently is credited with ‘a better explanation.’ This framework provides a more nuanced and defensible understanding of the literal sense with its locus in grammar, history and authorial intention as the normative one for doctrine and the pedagogical foundation for the ‘cathedral’ of spiritual senses. Chapter 2 demonstrates how true language about God can be saved through the Neoplatonic principle omne agens agit sibi simile, that effects share a likeness with their Cause. As Aquinas succinctly put it ‘we know that this proposition which we form about God when we say "God is," is true; and this we know from His effects’ (ST1.3.4.2.). Aquinas provides a metaphysics of being which addresses questions of perennial concern in a systematic and authoritative capacity. Chapter 2, in particular, uncovers Aquinas’ transformation of Dionysian language of hyperousios into his own predication of God as Ipsum Esse per se subsistens. I show how the inclusion of esse within his ontology is one reason why Aquinas’ metaphysics trumps postmodern and secular anti-metaphysics where something other than existence, such as potency, is posited as more basic, which is absurd. This chapter further demonstrates how the Byzantine essence/energies distinction, almost completely ignored in Western postmodern reception, illuminates the thought of Dionysius and renders some of his mysterious paradoxes more intelligible, but that this distinction is clarified within a more precise Chalcedonian Christology. Linked to the question of being in Chapter 2 are the importance of first principles of knowledge, discussed in Chapter 3. Aquinas clarifies a superior and more lucid account of knowledge than postmodern and pluralist receptions through his explicit recognition of the necessity of first principles, especially the Principle of Non-Contradiction. These are essential to ‘save knowledge’ from a slide into nihilism. Against postmodern receptions I show that the PNC is still retained even within the Corpus Dionysiacum, so that Aquinas’ reception is indeed exemplary. Chapter 3 essentially addresses an objection raised by the agnostic reception that if Dionysius is correct that God is ‘beyond being,’ then surely He is ‘beyond knowledge,’ and therefore ‘Super-unknowable?’ On this reading, negative theology is thus construed as an anti-philosophy to ‘the philosophy of Logos’ which seems on first glance to be compatible with Dionysius’ language of ‘unknowing.’ However, I show through primary sources that the Dionysian unknowing is still paradoxically a form of knowing but in a higher mode as Aquinas recognises. Thomas’ reception provides a rationally hopeful alternative to this agnostic stream which promises teleological fulfilment to the human instinct for intelligibility in the beatific vision which is to know God in his essence. This chapter brings a climax to the treatment of two streams of Dionysian reception, one characterised by strong agnosticism, from Plotinus’ account of the One ‘above’ Nous and therefore unknowable even to itself and the other following the ‘positive’ apophaticism of Augustinian orthodoxy which emphasises the Trinitarian Unity of the One and Nous by which the Cause can be known through His effects and through self-revelation. The difference has fundamental consequences for anthropology. We saw that Aquinas himself sees his project as saving Dionysius from ‘ a certain perverse interpretation’ (exemplified in Eriugena). One obvious strength of Aquinas’ reception is that he retains a metaphysical basis for essences including the essence of human person which is a necessary condition for science. A possible objectio is addressed in Chapter 4, regarding the exemplary nature of Aquinas’ reception in that he still values Dionysius metaphysical vision of hierarchy, an exceedingly unpopular vision today. This chapter attempts to show how Aquinas transforms and ‘saves’ hierarchy from negative connotations through recovering its original context of Goodness and love in which the contemplative ‘passes on’ the fruits of his contemplation to those receiving instruction and specifically through its basis in the metaphysics of primordial Beauty in which all things participate. Forgetting Aquinas, secularists have taken the false turn of assuming that nature does indeed act ‘in vain’ and as a result have lost philosophy’s birthing pool of wonder. As coextensive with both Nous and the Good, Beauty as a Divine Name provides a powerful and coherent counter-ontology to modern nihilism. The final section of this chapter on the greatness and limitations of Aquinas defends the Angelic Doctor by showing that even in those controversial but rare occasions where his reception is not true to the things in themselves (for example regarding the place of women, slaves or the Jewish people), his method of disputatio, from the emerging city universities and his commitment to the supreme authority of Scripture remains exemplary. This resists the zeitgeist (in which the idea of the university is in decline) by reaffirming the cognitive status of theology which flows from its origin in revelation. I show that Aquinas’ reception of the CD is superior to the postmodern reductive reframing of theology as theopoetics, since the term itself is parasitic on the philosophical theology which it denies and therefore to which it is not entitled. Aquinas’ reading of the CD is therefore a sharp weapon – a metacritique - against postmodern and secular thought.